Vestibular migraine in vertigo structure: modern views - O. V. Zaytseva; K. V. Overchenko; A. F. Khirnetkina (Лечащий Врач)
Existing approaches to treatment of patients with vestibular migraine were considered. All the approaches were based on the reports on the disease occurrences, retrospective cohort studies, and open tests. It was shown that further study of vestibular migraine was needed, basing on general diagnostic criteria.